Clinical response assessment after contact X-Ray brachytherapy and chemoradiotherapy for organ preservation in rectal cancer T2-T3 M0: The time/dose factor influence. (September 2020) - Benezery, Karen; Montagne, Lucile; Evesque, Ludovic; Schiappa, Renaud; Hannoun-Levi, Jean-Michel; Francois, Eric; Thamphya, Brice; Gerard, Jean-Pierre
Highlights: Treatment initiation of T2-T3 rectal cancers with Contact (CXB) provides a fast clinical complete response. In T2N0< 3 cm tumors, CXB first with chemoradiotherapy can achieve local control in more than 85%. The Phase III OPERA trial should bring robust data in favor of CXB as initial treatment of T2N0< 3 cm. Abstract: Introduction: A neoadjuvant treatment aimed at rectal preservation should achieve a clinical complete response. This study comparing neoadjuvant treatment initiated with Contact X-ray (CXB) or External Beam radiotherapy (EBRT) is evaluating the influence of the time/dose parameter on clinical response during the first six months. Materials and methods: This retrospective consecutive series included T2-3 rectal adenocarcinoma staged using digital examination (DRE), endoscopy, magnetic radiation imaging and/or endorectal ultrasound. All patients were treated with organ preservation intent. Treatment protocol combined CXB (80–110 Gy/3–4 fractions) and EBRT ± concurrent capecitabine. In tumor exceeding 3.5 cm treatment was often initiated using EBRT. Clinical response was assessed (DRE, proctoscopy ± imaging) at very close interval between 2 weeks and 6 months after treatment initiation. Results: Between 2002 and 2017, 61 patients (T2: 31; T3: 30) M0 (median age: 76 years) were treated. Treatment was initiated in 40 patients (T2: 28, T3: 12) with contact X-ray and in 21 (T2: 4, T3: 17) with EBRT. Using contact X-ray or EBRT first treatment, clinical complete (or near complete) response at week 14(±1) was respectively 88% [95CI:74–96] and 33% [95CI:15–57]. In multivariate analysis the treatment chronology was the most significant factor influencing cCR (OR: 7.53). At 6 months, with contact X-ray first all patients were in clinical complete response and five with EBRT remained in partial response. With 61 months median follow-up time, the local recurrence rate was 10% [95% CI: 6–16] at 5 years. T3 and fungating tumors were at higher risk of local recurrence. Organ preservation with good function was achieved in 95% of cases. Conclusion: This non randomized study tends to show that in early T2-3 tumors, a strategy using upfront contact therapy, which is reducing the overall treatment time, is an option allowing a more favorable outcome than EBRT first.